Design of a multivariable predictive controller for a coupled tank system - Kyaw, Thu Ya Aung. (2008)
Models are used in control systems for more than thirty years ago. Among them, Model Predictive Control (MPC) is one of the rather robust long range predictive control schemes, which has been widely used in industrial applications. This receding horizon method depends on predicting the plant's output over several steps based on assumptions about future control actions. Therefore MPC can be used either to control a "simple" plant with little prior knowledge or a more complex plant such as non-minimum-phase, open-loop unstable and having variable dead-time. The aim of this project is to model the real process of the system by using estimation techniques and then an design MPC controller.